Perception of Nursing Professionals in the care of people admitted to a Psychosocial Care Unit (Research, Society and Development, 2020)
In this context the study aimed to understand the perception of nursing professionals regarding the care provided to people hospitalized in a Psychosocial Care Unit. A qualitative methodological approach research, developed with 15 nursing professionals from a Psychosocial Care Unit, through semi-structured interview, in September 2015. For the data analysis, the Minayo Operative Proposal was used. The results reveal that the way of working is one of the influences in care, emphasizing the importance of multiprofessional teamwork. Stigmatization in Mental Health is another point, making professionals reflect on hospitalized people and their needs. Still, they report that the work in the area of Mental Health is satisfactory, because it is possible to obtain results from the care that is provided. It is concluded that the study presents contributions for nursing professionals to reflect on their practices and care, contributing to the production of knowledge enabling professionals, people with mental disorders, their families and society to understand a little more about the thematic.